Oligo-Carrageenan Kappa Increases C, N and S Assimilation, Auxin and Gibberellin Contents, and Growth in Pinus Radiata Trees - Moenne-Munoz, A; Contreras-Arredondo, R; Saucedo-Aguiar, S (Northeast Forestry University, 2015)
Oligo-carrageenans (OCs) obtained from pure carrageenans extracted from marine red algae stimulate growth by enhancing photosynthesis and basal metabolism in tobacco plants and Eucalyptus trees. In addition, OCs stimulate secondary metabolism, increasing the level of metabolites involved in defense against pathogens. In this work, we analyzed the effect of OC kappa on the increase in height, in activities of basal metabolism enzymes involved in carbon, nitrogen and sulphur assimilation, ribulose 1,5 biphosphate carboxylase/oxygenase (rubisco), glutamate dehydrogenase (GDH) and O-acetylserine thiol-lyase (OASTL), and in the level of growth-promoting hormones, the auxin indole acetic acid (IAA) and the gibberellin GA3, in pine (Pinus radiata) trees treated with OC kappa at concentrations of 1 and 5 mg mL−1 and cultivated for 9 months without additional treatment. Pines treated with OC kappa at 1 mg mL−1 showed a similar increase in height but displayed a higher increased in total chlorophyll, activities of rubisco, GDH and OASTL and level of IAA and GA3 than those treated with OC kappa at 5 mg mL−1. Thus, OC kappa stimulates growth and basal metabolism and increases the level of growth-promoting hormones in pine trees, mainly at 1 mg mL−1. © 2015, Northeast Forestry University and Springer-Verlag Berlin Heidelberg.